2012
DOI: 10.3177/jnsv.58.29
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Energy Density Is Inversely Associated with the Diet Quality Indices among Iranian Young Adults

Abstract: SummaryDietary energy density (DED) might be associated with the quality of the consumed diet. Therefore, this study was conducted to report the relationship between dietary energy density and diet quality index in Iranian youths. In this cross-sectional study we enrolled 410 female young adults in Isfahan-Iran who were selected according to the stratified random sampling method from among students of Isfahan University of Medical Sciences. A validated semi quantitative food frequency questionnaire was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
(25 reference statements)
4
20
0
1
Order By: Relevance
“…Additionally, in line with an earlier study among Iranians, calcium and fiber intakes were lower among those in the highest tertile, wheras DED was higher compared to those in the lowest tertile [31]. An inverse association for calcium intake and DED with BMI and WC was well established [14,22,60]. Another possible reason may be related to the high glycemic index of white rice [61] and lower content biologically active agents, which could adversely affect body weight and WC [62].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Additionally, in line with an earlier study among Iranians, calcium and fiber intakes were lower among those in the highest tertile, wheras DED was higher compared to those in the lowest tertile [31]. An inverse association for calcium intake and DED with BMI and WC was well established [14,22,60]. Another possible reason may be related to the high glycemic index of white rice [61] and lower content biologically active agents, which could adversely affect body weight and WC [62].…”
Section: Discussionsupporting
confidence: 85%
“…For example, consumers of whole grains have higher diet quality indices [35]. In our previous study among female youth, higher DED was associated with higher energy and carbohydrate consumption and lower fiber intake, MAR, and NARs for calcium and vitamins B12, B2, and C [14]. Increased fiber intake is a recommended strategy to reduce DED [35,36].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Also, results of an Iranian study conducted in young females supported our findings regarding carbohydrate [22]. Moreover, previous study reported that subjects who had low energy-dense diet consumed higher amounts of zinc, calcium, vitamin C, and vitamin B2 [23]. As patients in the first tertile of DED consumed more amounts of dietary fiber, it was suggested that large amounts of consumed carbohydrate were from fruits, vegetables, and whole grains.…”
Section: Discussionsupporting
confidence: 81%